2016
DOI: 10.1177/0899764016649693
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Nonprofits’ Revenue Composition and Their Economic-Financial Efficiency

Abstract: We study financial efficiency in the nonprofit sector and document that organizations that rely mainly on commercial revenues are more efficient in managing their overhead and administrative expenses compared with nonprofits that rely mainly on donations. We also record a positive relationship between the extent of a nonprofit's reliance on donations and its efficiency in generating them. Our findings suggest economies of scale in the nonprofit sector and also a positive (negative) relationship between receivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 18 publications
2
65
2
1
Order By: Relevance
“…Some researchers point out that strategic planning determines NGOs' performance (Bryson 2018;Allison and Kaye 2011). Others even argue that organizations relying primarily on commercial revenues are more efficient in managing their overheads and administrative expenses than are the nonprofits which rely mainly on donations (Ecer et al 2017).…”
Section: Conclusion and Further Research Directionsmentioning
confidence: 99%
“…Some researchers point out that strategic planning determines NGOs' performance (Bryson 2018;Allison and Kaye 2011). Others even argue that organizations relying primarily on commercial revenues are more efficient in managing their overheads and administrative expenses than are the nonprofits which rely mainly on donations (Ecer et al 2017).…”
Section: Conclusion and Further Research Directionsmentioning
confidence: 99%
“…For example, Andreoni and Payne's () study of U.S. arts and social service organizations and Hughes, Luksetich, and Rooney's () study of U.S. symphony orchestras demonstrate that government funding leads to significant reduction in nonprofit fundraising expenditures. Ecer et al () examined the effect of nonprofits' revenue composition on their efficiency and reported that U.S. charities receiving more government grants generally have lower overhead costs (i.e., administrative and fundraising expenses). With the savings from administrative and fundraising expenditures, nonprofits could devote more resources to mission‐related outputs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast, resource dependence theory (or coercive isomorphism theory) suggests that government-funded nonprofits have to devote substantial resources to conforming to the program and accounting requirements involved in applying for and managing government funding, leading to increased administrative expenses at the cost of program expenses (DiMaggio & Powell, 1983;Pfeffer & Salancik, 1978). Previous empirical studies have reported mixed results (Alexander et al, 1999;Ecer, Magro, & Sarpça, 2017;Grønbjerg, 1993;Sloan & Grizzle, 2014;Thornton, 2014). The key concern underlying this debate is how government funding affects nonprofits' capacity to carry out their missions, which further connects to a fundamental question about how government actions influence the role of the nonprofit sector in democratic societies.…”
Section: Introductionmentioning
confidence: 99%
“…Dicha fuente puede complementar a las anteriores, pues su volatilidad es inferior y proporciona una mayor autonomía, aunque, no obstante, se encuentra condicionada por el tamaño de la ENL y el subsector de actividad, así como por la posible pérdida de los valores distintivos del sector no lucrativo (Froelich, 2999;Maier et al, 2016). Ecer et al (2017) muestran cómo las ENL en las que el peso de esta fuente de ingresos es mayor consiguen una mayor eficiencia administrativa, mientras que Keating, Fischer, Gordon y Greenlee (2005) obtienen que dichas organizaciones tienen un menor nivel de vulnerabilidad financiera, y Álvarez-González et al (2017) que en tales ENL se intensifica el efecto positivo en las relaciones entre las colaboraciones con las empresas, el marketing interno y la performance de la organización.…”
Section: Características E Importancia De Las Fuentes De Ingresos En unclassified